Analisis Strategi Segmentasi, Targeting Dan Positioning Terhadap Efektivitas Pemasaran Pt. L'oreal Indonesia - Erli Azzahra Putri; Emil Salim; Della Asmaria Putri (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of Segmentation, Targeting, and Positioning (STP) strategies and their impact on the marketing effectiveness of PT L'Oréal Indonesia. The Indonesian cosmetics industry is experiencing significant growth with increasingly fierce competition between global and local brands. This research uses a descriptive qualitative method with SWOT analysis and STP analysis approaches. Data were collected through documentation studies, observations, and literature reviews related to L'Oréal Indonesia's marketing strategies for the period 2020-2025. The results show that PT L'Oréal Indonesia has implemented STP strategies comprehensively through demographic, geographic, and psychographic segmentation with a differentiated marketing approach for various brands in its portfolio. However, marketing effectiveness still faces challenges from the dominance of local brands that are more adaptive to Indonesian cultural values such as halal and emotional closeness. SWOT analysis shows that the company is in a strategic position to implement aggressive growth strategies by leveraging global brand strength and large market opportunities. This study concludes that STP strategies have a positive effect on marketing effectiveness, but require further adjustments to local consumer preferences to increase competitiveness in the Indonesian market.